Friendly-Tourism By TV Media : Encouraging Local Wisdom Of East Java - Roziana Febrianita; Aldi Purnomo (Jurnal Ilmu Komunikasi, 2019)
Television as one of the mass media in some way still being capable ofproviding an important role in the growth, development, and promotion of tourismby enhancing awareness and understanding toward the necessities in the local andglobal scale of the tourism industry. In an absolute way, the concern of thetelevision in this context is visualized in various aspects of life and becomingincreasingly greater day by day, especially in the sphere of influence; such as socialinteraction, and cultural also educational aspects. These can articulate thetraditions, customs, and heritage of the past, the coverage of television may attemptto correct any widespread erroneous information in this post-truth era. Thus thispaper focus on how TV media set tourism coverage in conveying local wisdom ofEast Java. The method used in this paper is qualitative, combining two methods ofdata collecting, interview, and content analysis. Interview performed on coverageteam, henceforward content analysis is proceeded on tourism coverage by InsideIndonesia, a program of CNN Indonesia episode “Wajah Baru KuntulanBanyuwangi”. The research findings are: (a) TV tourism coverage providesfriendly-tourism sources of information, also (b) accomplish a balance conduitamongst disaster phenomenon and tourism sector, and last but not least (c)converse the local wisdom in the global perspective of tourism coverage.